The effect of titanium dioxide nanoparticles on the bond strength between maxillofacial silicone and acrylic core - Abdullah Jasim Mohammed; Ahmed Asim Al-Ali; Omar Abdul Mohsin Sheet (Romanian Journal of Stomatology)
Objectives. This study was aiming to evaluate the influence of Titanium dioxide nanoparticles addition on the bonding performance of platinum primer (G611) between maxillofacial silicone and acrylic substrate. Materials and methods. 180 samples were divided on two tests (shear and peel bond strength) and they were divided into two main groups (cold cure, and 3D printed) acrylic resins. Each group was subdivided into 5 subgroups (N=9) according to the concentration of nano-filler addition (0%, 0.5%, 1%, 1.5% and 2%) by weight. The data obtained were evaluated by one-way ANOVA and Tukey's post hoc tests at P˂0.05. Results. Statistical analysis revealed (0.5% and 1%) concentrations had significantly the highest bond strength in both groups, whereas (2%) had the lowest bond strength in both groups. Conclusion. Reinforcement of the platinum primer G611 with Titanium dioxide (TiO2) nanoparticles (1%) concentration by weight resulted in a significant improvement in the bonding performance of the platinum primer G611 larger concentrations (1.5%, and 2%) resulted in declining bonding strength.